ABNORMAL BEHAVIORS IN OKKY MADASARI’S NOVEL BOUND IN THE PERSPECTIVE OF PSYCHOLOGICAL PROBLEMS - Fatma Khairani Harahap; Safitri Hariani (JOURNAL OF LANGUAGE, 2023)
This research aimed to describe the abnormal behavior and the factors causing the abnormal behavior experienced by the first character in Okky Madasari's novel Bound. The qualitative-descriptive study was used in this research. The research focused on the problems related to the Sasana’s abnormal behaviors. Sasana is the first character in the novel. The abnormal behaviors in the novel were analyzed by implementing the abnormal psychology. The data collection techniques used in this study were reading and note-taking techniques. The depiction of the abnormal behaviors experienced by the first character, and the factors of the behaviors are described based on the collected data both in the form of sentences and paragraphs contained in the data source. The results show that the abnormal behaviors happen to the first characters in the novel. The abnormal behaviors in this novel include being interested in things related to women, wearing women's clothes, behaving like a girl, and feeling jealous of his sister. Besides, the factors that cause the abnormal behaviors of the first character are biological factors and socio-cultural factors.